Anti Nociceptive, Anti Inflammatory and Anti Bacterial Properties of Leaf of Female Borassus flabellifer (Arecaceae) - Otilia Banji, Chaitanya R.S.N.A.K.K, Sandhya S*, Sudhakar K, David Banji (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The Borassus flabellifer is a tall, erect palm, easy to recognize by its large, fan-shaped leaves. The different parts of the plant are used for ailments like secondary syphilis, antiperiodic, heart burns, liver, inflammation and spleen enlargement. The chemical constituents include gums, albuminoids, fats, steroidal glycosides and carbohydrates like sucrose. In the present work anti nociceptive, anti inflammatory, membrane stabilizing property, and anti microbial activities were carried out. The dried leaf powder was extracted with ethanol and submitted to chemical tests. It revealed the presence of saponins, flavonoids, steroids and tannins.Â In the anti nociceptive activity Eddyâ€™s hot plate method and tail immersion method were performed using tramadol as the standard. The leaf extract has shown a potent nociceptive activity for both the evaluation parameters.Â Carrageenan induced rat paw edema and HRBC membrane stabilizing property were performed for the anti inflammatory activity using diclofenac sodium and hydrocortisone as the standard drugs. The results showed that the ethanolic leaf extract exhibited potent anti inflammatory activity and membrane stabilizing property in a dose dependent manner. The antibacterial screening was performed on the organisms Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumonia using gentamycin as the standard. In the antibacterial activity the leaf extract was found to be not effective in inhibiting the growth of bacterial strains.